PENGARUH MODEL KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR TEMATIK KELAS IV SEKOLAH DASAR - Devy Purwanti; Tahmid Sabri; Dyoti Auliy (Universitas Tanjungpura, 2020)
AbstractThis study aims to determine the effect of the use of jigsaw cooperative medel type on thematic learning on cognitive learning outcomes of fourth grade students at SD Mujahidin, South Pontianak. The model used in this study is a quasi-experimental experimental research design, with the experimental design of nonequivalent control group design. The population of this study was all grade IV students of the South Pontakan Mujahidin Elementary School. The sample in this study there are 2 classes namely class IVb and class IVe, the technique used to take samples is purposive sampling technique. To determine the experimental class and control class seen from the per-test value by drawing the IVB class as many as 30 students as the control class and IVE as many as 28 students as the experimental class. Data collection techniques using measurement techniques. The instrument used was a test sheet in the form of multiple choice learning questions totaling 45 questions. Based on calculations obtained an average post-test learning outcomes of the control class 63.32 and the average post-test learning outcomes of the experimental class 71.24 so that the 2.4984 post-test data were obtained with a table for the level of significance (α = 5 % and dk = 30 + 28-2 = 56) from 2.0042, because tcount> ttable then Ha is accepted, this proves that there is an influence of the jigsaw type cooperative model on thematic learning towards the learning outcomes of grade IV students at SD Mujahidin, South Pontianak. From the results of the calculation of the effect size obtained by 0.52 including medium criteria, so it can be concluded that the cooperative type of jigsaw in thematic learning has a moderate effect on the learning outcomes of grade IV elementary school students in South Pontianak Mujahidin. Keywords : Jigsaw type cooperative models, Learning outcomes, and Thematic learning